Goblet cell appendiceal tumors – Management dilemmas and long-term outcomes. (March 2015) - Rossi, Roberta Elisa; Luong, Tu-Vinh; Caplin, Martyn Evan; Thirlwell, Christina; Meyer, Tim; Garcia-Hernandez, Jorge; Baneke, Alex; Conte, Dario; Toumpanakis, Christos
Abstract Background Appendiceal Goblet cell tumors (GCTs) are clinically more aggressive, and have a worse outcome than midgut neuroendocrine tumors (mNETs). Guidelines for management of GCTs are limited. Methods A retrospective case-study analysis was performed in patients with a diagnosis of GCT, confirmed on histological review. Patients were evaluated clinically, biochemically, and radiologically. Results 48 patients were identified (TNM stage I–II: 27, stage III: 15, stage IV: 6). Median follow-up was 44 months and was complete in all patients. 68.8% presented with acute appendicitis. 44/48 patients had initial appendectomy, followed by prophylactic right hemicolectomy in 41. 10/48 patients had recurrent disease [median time to recurrence 28 months (range 4–159)]. Of those, 9 received systemic chemotherapy (FOLFOX/FOLFIRI), which was also given in 5/48 patients with disseminated disease at diagnosis. Partial response, stable disease and disease progression was noted in 22%, 22% and 56%, respectively. Adjuvant chemotherapy was also administered in 9/48 patients with stage III disease after right hemicolectomy, however in 3/9 the disease recurred. Median progression/disease-free-survival was 44 months (range 3–159) and overall 5-year survival rate was 41.6%. Conclusions The clinical behaviour of GCTs is more similar to colorectal adenocarcinomas than to NETs. A prophylactic right hemicolectomy is recommended to reduce the risk of recurrence. Systemic chemotherapy, using colorectal adenocarcinoma regimens, is indicated for advanced or recurrent disease and has encouraging results. Prospective studies are needed to define the role of adjuvant chemotherapy and the optimal chemotherapy regimen.